2021
DOI: 10.3390/ma14082067
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Mechanism, Microstructure, and Mechanical Properties Evolution of Mg–Gd–Y–Zr Alloy during Cold Torsion

Abstract: Mg–Gd–Y–Zr alloy was subjected to torsion of various strain levels at room temperature. Obvious traces of basal slip were observed in the twisted alloy. Dislocations of <c+a> were also observed, but there were no signs of significant sliding. Even in the sample whose equivalent strain became 0.294, 101¯0 twinning and 101¯2 twinning were rarely seen. The deformation mode with predominant basal <a> dislocations and subordinate <c+a> dislocations resulted in a modified Y fiber texture with a bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Considering Reaction (10), the reduction of Cr 2 O 3 proceeds at 1263 • C. It is worth noting that during Reactions ( 8)-( 13), hot CO gas is continuously generated which permeates from the smelting zone upwards through the furnace bed. The hot CO gas acts as a reductant, partially reducing chromite [69]. The effect of CO(g) partial pressure was, however, not considered here.…”
Section: Thermodynamic Considerationsmentioning
confidence: 99%
“…Considering Reaction (10), the reduction of Cr 2 O 3 proceeds at 1263 • C. It is worth noting that during Reactions ( 8)-( 13), hot CO gas is continuously generated which permeates from the smelting zone upwards through the furnace bed. The hot CO gas acts as a reductant, partially reducing chromite [69]. The effect of CO(g) partial pressure was, however, not considered here.…”
Section: Thermodynamic Considerationsmentioning
confidence: 99%
“…28 In the Mg-Gd alloy, gadolinium ions are doped instead of magnesium ions into the hydroxide layer to improve corrosion resistance. 29 Zinc and strontium ions not only act as trace elements involved in normal material metabolisms in the human body, but also help express the markers of early osteogenic differentiation such as COL-I and ALP. Moreover, the addition of zinc ions enhances the ductility and plasticity of the magnesium alloy, causing the alloy to adopt a complex shape and contour to match an anatomical site.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that rare earth (RE) elements alloying is the most useful modification treatment to enhance mechanical properties of Mg alloys [ 4 ]. In recent years, numerous researches have been focused on Mg alloys with heavy RE elements, as an illustration of the Mg-Gd-Y-Zr [ 5 , 6 , 7 ], Mg-Gd-Y-Zn-Zr [ 8 ], Mg-Yb-Gd-Zn-Zr [ 9 ] and Mg-Gd-Y-Nd-Zn-Zr [ 10 ] alloys are developed, and these alloy usually exhibits excellent mechanical properties. However, the high content of heavy RE elements in matrix alloy increases the cost of alloys and reduces the advantages of lightweight structural alloy materials.…”
Section: Introductionmentioning
confidence: 99%